LITURGIA E IDENTIDADES CULTURAIS NAS PRÁTICAS LITÚRGICAS DA IGREJA PRESBITERIANA-REFORMADA EM CUBA NA PERSPECTIVA DA PRÁXIS RELIGIOSA - Celorrio, Pedro Julián Jiménez (2010)
This thesis tackles the relationship between liturgy and cultural identities manifested throughout the different liturgical practices displayed by the Reformed- Presbyterian Church of Cuba (RPCC). The study is constructed from the perspective of the religious praxis. It refers to those activities developed by the Christian churches and institutions which convey creation, liberation and a radical transformation of individual, nature and society. The text tackles the social and cultural history of the country and the history of Cuban Presbyterianism, focusing on the period from 1967 to 2009. It takes into account four specific objectives: investigation of the cultural matrixes that formed the Cuban culture, description of the protestant historical roots and streams within Cuban Presbyterianism until the organization of the RPCC, presentation of the liturgical practices of the RPCC, and construction of guide lines for the celebration of hope throughout an inculturated liturgical praxis. These objectives were accomplished by using a historical method, which investigates events and institutions from the past in order to verify its influences in society, and by means of a bibliographical methodology that is supplemented by an investigation of the field and a questionnaire that covers twelve aspects of liturgy. Among other procedures, five specific actions were developed to the elaboration of the final text: examination of literature produced by Cuban and non Cuban authors related to the theme of this dissertation, organization of the texts, application of the interviews and evaluation of the results. In this thesis the author seeks to provide answers to a particular problem: the society changes, however, the church does not develop an efficient dialogue with it, nor does it follow the social changes that are occurring in its midst. This leads to the question: What can be done so that the Church could adjust its liturgical praxis to the socio-cultural context in which it is acting? The proposals raised at the end are not presented as a rigid pattern, but as a guide or map which must constantly be revised and adapted.